Language and rules : a normative approach to the myth of the given - Giromini, José (2015)
The aim of this paper was to show that the specifically epistemological and semantic failures of the Myth of the Given are a result of mistaken normative assumptions. The self-authenticating awareness of particulars and the self meaning-giving semantic rules are different disguises wore over a skeleton of a normative self-moving mover. The first episode I narrated was but a pure form of the third. Whatever his solution may be, we owe to Wilfrid Sellars the philosophical miracle –opposite to the theological– of turning three problems into one.